THE ANALYSIS OF STUDENT ANXIETY WHEN SPEAKING ENGLISH (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
Speaking is one of the vital skills that students should master, alongside reading, writing and listening. By speaking, students are able to deliver messages directly and communicate with each other. Speaking is often seen as the most common method of communication, which is why students who learn foreign languages, such as English, should master this skill. But for some students, they still find difficulties and feel anxious when they try to speak English in public. The writer conducts this research to find the factors or what cause the students’speaking anxiety. This research is using study case of qualitative research method . There are particular reasons and factors that cause student anxiety when speaking English.
Keywords: speaking; anxiety; qualitatie research